SSA challenge program: Lake Kivu pilot learning site: review of the Lake Kivu pilot learning site project and purpose of the meeting - Nyamwaro, Sospeter S.; Buruchara, Robin Arani (International Center for Tropical Agriculture, 2010)
Remarks on Review of the Lake Kivu Pilot Learning Site project and purpose of the meeting at the Cross-site Regional Review Meeting of the LKPLS, 12-15, July 2010, Kabale, Uganda